Digitalisasi Terhadap Efektivitas Transaksi UMKM Di Indonesia Perspektif Ekonomi Islam - Toon, Fadiah; Andi Jahnur Itsnaieni Kaffah (Yayasan Darussalam Patalassang, 2025)
Digitalization in the payment system has become an important part of the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This study aims to analyse the role of digitalization in improving the effectiveness of MSME transactions and its impact on economic growth. Using a qualitative descriptive approach, this research relies on primary data obtained through interviews with MSME players in Makassar City as well as secondary data from various literatures and official reports. The results show that digital transactions provide convenience for MSMEs in expanding markets, improving operational efficiency, and accelerating economic growth. Thus, digitalization is a strategic solution in improving the competitiveness of MSMEs at the national and global levels.